Atypical Localization of Pyogenic Granuloma on the Upper Lip: A Case Report - Annisa Astari; Riana Miranda Sinaga (GLOBAL HEALTH SCIENCE GROUP, 2025)
Pyogenic granuloma is a benign vascular tumor that commonly arises following minor trauma, irritation, or hormonal influences. Although frequently found on the gingiva, hands, or face, localization on the upper lip is considered uncommon. This case report aims to describe the clinical presentation, diagnostic features, and therapeutic outcome of pyogenic granuloma in an unusual location. A 16-year-old girl presented with a two-month history of a red, painless nodule on the upper left lip. The lesion initially appeared as a wound that gradually enlarged and occasionally bled following minor trauma. The patient had been using orthodontic braces for the past four months. Dermatological examination revealed a solitary erythematous papule measuring 0.3 cm with a stalk and crust. Histopathological examination revealed slit-like proliferative blood vessels and inflammatory infiltrates, confirming the diagnosis of pyogenic granuloma. The lesion was treated by shave excision followed by electrocautery. Clinical improvement was observed, with complete resolution of the lesion at the 10-day follow-up. This case underscores the importance of clinical vigilance in recognizing pyogenic granuloma at atypical anatomical sites and demonstrates the effectiveness of shave excision combined with electrocautery as a treatment modality.